معوقات المشاركة السياسية للمرأة في الجزائر وآليات الحد منها: دراسة تحليلية - بوعافية، العيد; بلقاسم، الحاج (جامعة الأمير عبد القادر للعلوم الإسلامية - كلية أصول الدين, 2021)
يأتي بحثنا هذا ليبين أهم المعوقات التي تحول دون مشاركة المرأة في اتخاذ القرارات السياسية، أو ممارسة نشاطات ذات علاقة بالسياسة، سواء كناخبة أو كمترشحة، على مستوى تمثيل الشعب في المجالس البلدية، أو الولائية، أو حتى الاستحقاقات الرئاسية. إن موضوع المشاركة السياسية بالنسبة للمرأة لا يزال يطرح مجموعة من التساؤلات في ظل الانفتاح على العالم الخارجي، وتطور المسار الديمقراطي على المستوى العالمي، إذ لم يعد هناك إشكال في ما يخص الفرق بين الرجل والمرأة في الدول الغربية، بل العبرة عندهم بالكفاءات والشهادات دون اعتبار لمسألة الجنس البشري، غير أن المجتمعات العربية لازالت تنظر إلى المرأة على أنها محدودة المسؤوليات، فمجرد مشاركتها في الانتخابات يعتبر إنجازا في حد ذاته بالنسبة لهذه المجتمعات. وتوصلت الدراسة إلى النتائج الآتية: - هناك معوقات اجتماعية وثقافية تقلل من المشاركة السياسية للمرأة. - ضعف قواعد استقلالية المرأة وتبعيتها الدائمة للرجل مما يزيد من صعوبات مشاركتها المستقلة وتمثيلها المستقل.
Our research highlights the most important obstacles to women's participation in political decision-making, or political-related activities, whether as a voter or as a candidate, at the level of people's representation in municipal, state, or even presidential entitlements. The issue of political participation for women continues to raise a range of questions in the light of the openness to the outside world and the development of the democratic process at the global level, since there is no longer a problem with the difference between men and women in Western countries, but rather the lessons ought by them by competencies and testimonies without regard to the question of the human race, but Arab societies still view women as limited responsibilities, as the mere fact that they participate in elections is an achievement in itself for these societies. The study reached the following conclusions: - There are social and cultural constraints that reduce women's political participation. - The weakness of women's independence rules and permanent dependence on men, which increases the difficulties of their independent participation and independent representation.
Keywords: المشاركة السياسية -- المرأة الجزائرية -- حقوق المرأة -- القضايا السياسية